Clinical Pharmacy Services and Workforce Requirements at MOH Hospitals during Ten years Mass Gathering Hajj (2006-2015) in Makkah and Al-Madina Regions, Saudi Arabia - Alomi, Yousef Ahmed; Alhennawi, Khairat; Khayayt, Nizar (Journal of Pharmacy Practice and Community Medicine)
Purpose: To explore the clinical pharmacy services and workforce requirements at Ministry of Health Hospitals during mass gathering Hajj over ten years (2006-2015) at Makkah and Al-Madina Regions in Saudi Arabia. Methods: It is a retrospective analysis of ten years (2006-2015) of MOH hospital pharmacies during mass gathering Hajj period (15-30 days). The clinical pharmacist should provide pharmaceutical to all patients either Pilgrim or not Pilgrim at Makkah region. It included Mona holy places hospitals; Arafat holy places hospitals, and Makkah city. The workforce requirements calculated based on MOH workforce standards of hospitals. The clinical activities drive from MOH critical care services, and emergency services, and mortality rate data. The nine clinical pharmacy services characterized by reduction mortality cost saving and mass gathering demand chosen. American College of Clinical Pharmacy (ACCP) model of clinical activities used. Results: The total number of Pilgrims was (1,952,817 3,161,573) with average of (2,445,208.1). The mean number of clinical pharmacists needed was (22.31 FTE) per each hospital at Makkah. The average number of clinical pharmacists needed was (18.71 FTE) per hospital in Al-Madina. The central clinical pharmacy needs (4.31FTE) of clinical pharmacist per each hospital in Makkah region. In Al-Madina region demand was (2.71 FTE) of clinical pharmacists. The patient-centered clinical pharmacy services need (12 FTE) of clinical pharmacist per each hospital at Makkah and Al-Madina regions. The administrative, clinical pharmacy activities need (4 FTE) of clinical pharmacist per each hospital at Makkah region, while (2 FTE) at Al-Madina. Conclusion: The clinical pharmacy services are essential during mass gathering Hajj period. The clinical pharmacy services prevent drug-related mortality and morbidity during Hajj period. Also, improve patient clinical outcome, patient quality of life, and avoid the unnecessary cost.
Keywords: Clinical pharmacy; Workload; Workforces; Mass Gathering; Hajj; Makkah; Al-Madina; Ministry of Health